2004
DOI: 10.1002/mabi.200400096
|View full text |Cite
|
Sign up to set email alerts
|

Significant Role of Bacterial Undecaprenyl Diphosphate (C55‐UPP) for Rubber Synthesis by Hevea Latex Enzymes

Abstract: Washed bottom fraction (BF) membrane-bound particles of centrifuged fresh Hevea latex were found to be very active in rubber biosynthesis (RB). The washed BF membrane (WBM) showed higher RB activity and is strongly stimulated by anionic surfactants--more by DOC than SDS. WBM enzymes system can synthesize rubber either with allylic isoprenes (higher RB) or without (lower RB). Washed rubber particles (WRP), used generally in RB assays, had very low RB activity compared to the much higher activity observed for WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The mechanism of the biosynthesis of NR molecules is still not completely understood since the initiation, growth, and termination processes are complicated, and many different kinds of proteins are involved. Although various polymerization mechanisms have been proposed,4, 16–18 it is now confirmed that the polymerization occurs at enzyme proteins on the surface of the membranes surrounding the rubber particles. Therefore, several kinds of proteins exist in the NR latex, and many of them remain in the raw rubber.…”
Section: Resultsmentioning
confidence: 97%
“…The mechanism of the biosynthesis of NR molecules is still not completely understood since the initiation, growth, and termination processes are complicated, and many different kinds of proteins are involved. Although various polymerization mechanisms have been proposed,4, 16–18 it is now confirmed that the polymerization occurs at enzyme proteins on the surface of the membranes surrounding the rubber particles. Therefore, several kinds of proteins exist in the NR latex, and many of them remain in the raw rubber.…”
Section: Resultsmentioning
confidence: 97%
“…In the H. brasiliensis genome, we identified 18 genes encoding enzymes for the MVA pathway and 29 for the MEP pathway. For the initiation of rubber biosynthesis, a priming allylic diphosphate (farnesyl diphosphate, geranylgeranyl diphosphate, or undecaprenyl diphosphate) is needed [36]. The biosynthetic pathway leading to these compounds involves 5 enzymatic steps encoded by 21 genes in the assembly.…”
Section: Resultsmentioning
confidence: 99%